2009
DOI: 10.1021/la904180u
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Headgroup on Electrical Conductivity of Self-Assembled Monolayers on Mercury: n-Alkanethiols versus n-Alkaneselenols

Abstract: The relative efficiencies of electron tunneling across self-assembled monolayers (SAMs) of n-alkanethiols and n-alkaneselenols, CH(3)-(CH(2))(n)-XH, where n = 8, 9, 11, and X = S or Se, deposited on mercury electrodes were measured via electroreduction of Ru(NH(3))(6)(3+) in aqueous solutions. Electron tunneling rates across the monolayer films decay exponentially with the monolayer thickness with a tunneling coefficient, beta = 1.1 +/- 0.1 per CH(2) irrespective of the identity of the -XH headgroup. Electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…Particularly prominent examples of metal–molecule contacting groups include thiols [4647], selenols [4849], dithiocarbamates [5051], carbodithioates [52], amines [5354], esters [55], cyano [5657], isocyanides [58], nitriles [59], carboxylic acids [24,55,60], dithiocarboxylic acids [52], isothiocyanates [61], dimethylphosphine [62], 4-(methylthio)phenyl groups [63], dihydrobenzo[ b ]thiophenes [64], thienyl rings [65], diphenylphosphine group [66], trimethylsilylethynyl groups [6769] and fullerenes [60,7071]. However, many of these groups have significant limitations including chemical degradation at working temperatures [7273], associated polymerization phenomena [74], small binding energies [74], unexpectedly high contact resistance [7580], and multiple conductance values due to the variability in the binding geometries [8186].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly prominent examples of metal–molecule contacting groups include thiols [4647], selenols [4849], dithiocarbamates [5051], carbodithioates [52], amines [5354], esters [55], cyano [5657], isocyanides [58], nitriles [59], carboxylic acids [24,55,60], dithiocarboxylic acids [52], isothiocyanates [61], dimethylphosphine [62], 4-(methylthio)phenyl groups [63], dihydrobenzo[ b ]thiophenes [64], thienyl rings [65], diphenylphosphine group [66], trimethylsilylethynyl groups [6769] and fullerenes [60,7071]. However, many of these groups have significant limitations including chemical degradation at working temperatures [7273], associated polymerization phenomena [74], small binding energies [74], unexpectedly high contact resistance [7580], and multiple conductance values due to the variability in the binding geometries [8186].…”
Section: Introductionmentioning
confidence: 99%
“…28À32 Recent studies suggest that contact resistance of the anchor group is of crucial importance for the electronic transport in molecular junctions. 30,31 The preparation procedures to obtain high quality SAMs (single, compact and ordered phase) for simple molecules such as thiols are basically well-established for surfaces such as gold and silver. 10À32 It is interesting to note that SAMs of alkanethiols on the surface of liquid mercury possess a significantly different structure as compared to that on a gold surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[82][83][84] Although not probed in a Au-SAM/Hg junction, Adaligil et al measured values of b across SAMs of alkanethiolates and selenates using redox couples with SAMcoated working electrodes and found that, in fact, the rate of tunneling was about four times higher across S-Au than it was across Se-Au. [85] Von Wrochem et al formed SAMs by exposing diamines to CS 2 in the presence of an Au substrate. [86] The resulting SAMs are anchored by dithiocarbamates, which form in situ, creating an anchoring group comprising two thiol atoms.…”
Section: Non-thiol Systemsmentioning
confidence: 99%